Plasticity and partitioning of foraging behaviour among and within sympatric Pygocelis penguin populations - de Kock, Leandri (Department of Statistical Sciences, 2025)
Central-place foragers, such as breeding seabirds, need to adjust their foraging behaviours in response to the growth and development of their offspring. As a result, they need to return to their nests regularly. These breeding constraints limit their foraging ranges. In the Southern Ocean, sympatrically breeding penguin species often have overlapping foraging ranges and niches that may lead to competition. Interspecific (between species) and intraspecific (within species) competition are important processes that may shape the foraging behaviours of penguins. However, competition pressure may vary with changes in environmental conditions across several scales (e.g. between years or within breeding seasons as a function of fluctuating central-place foraging constraints). This dissertation aimed to determine how the foraging behaviour of two closely related and cooccurring seabird species - chinstrap (Pygoscelis antarcticus) and gentoo (P. papua) penguins – differ among and within populations. I analysed high-resolution location (GPS) and dive data from 221 individuals breeding at two sites (Nelson Island and Kopaitic Island) in the West Antarctic Peninsula during the 2018/19 austral summer. These sites are characterised by different environmental conditions and penguin population sizes, two factors that may influence foraging behaviours and niche partitioning. The first chapter includes a general background of the study and the dissertation's aims and objectives. In the second chapter, I investigated intraspecific phenotypic plasticity of foraging behaviours among and within these penguin populations. In a subsequent chapter, I quantified foraging niche separation and identified factors that modify interspecific niche separation between chinstrap and gentoo penguins at the two sites. To test whether penguins exhibited phenotypic plasticity in foraging trip distances and duration, and to partition diving behaviours (e.g. maximum dive depth) among and within populations, I fitted a series of generalized linear mixed-effects models with species, site, breeding stage (incubation, brood and crèche) and environmental variables as covariates. In addition to comparing foraging behaviours between populations, my analysis quantified how individuals differed in their average behavioural expression using a repeatability index. I used an autocorrelated kernel density estimate approach to quantify space use and overlap between species as breeding transitioned from incubation to brood and crèche. Sites greatly influenced both species' foraging behaviours, with the Kopaitic Island environment being a colder, saltier environment which may be more suitable for foraging. Chinstrap penguins, which prey almost exclusively on Antarctic krill (Euphausia superba), along with gentoo penguins (dietary generalists) showed plasticity in foraging trip and dive behaviours between sites and breeding stages. During brood and crèche, chinstrap penguins contracted their foraging ranges and dived deeper, increasing niche overlap and opportunity for interspecific competition with gentoo penguins. Foraging niche overlap was influenced by site-specific environmental conditions. For example, warmer seasurface temperatures (which correlate with increased diving depths) and shallower bathymetry (which limits diving depth) at Nelson Island reduced opportunity for niche separation between the two species, especially during the brood and crèche stages of the breeding season. My results show that chinstrap and gentoo penguin foraging behaviours are plastic depending on site and breeding stage. Furthermore, my results show that seasonal changes in central-place foraging constraints and environmental conditions can modulate niche separation between these co-occurring species. A continuation in climate change (e.g. further warming sea temperatures) in this region of the Southern Ocean is expected to impact penguin prey distribution, which will likely lead to changes in foraging behaviour and niche overlap of chinstrap and gentoo penguins. While chinstrap and gentoo penguins may adjust their foraging behaviour to adapt to changing environmental conditions, these changes may have consequences for population dynamics and the future distribution and abundance of these species.